OP10 Effects of socio Economic Position in Childhood and Adulthood on Cardiometabolic Risk Factors: The Jerusalem Perinatal Family Follow-Up Study. (17th September 2012) - Manor, O; Savitsky, B; Hochner, H; Meiner, V; Siscovick, DS; Friedlander, Y
Abstract : Background: Studies indicate that Socio Economic Position (SEP) might be an important predictor of cardiometabolic disease mortality and morbidity; yet the importance of timing of the effect of SEP on cardiometabolic risk factors has not been fully established. Our aim was to assess the independent effect of SEP in both childhood and adulthood on cardiometabolic risk factors in young adults and to examine potential interactive effects of SEP at both time points on these risk factors. Methods: This is a prospective follow-up of 1132 individuals, born in Jerusalem between the years 1974–76, to young adulthood with bio-medical data at mean age 32. Outcomes include Body Mass Index (BMI), Waist to Hip Ratio (WHR), blood pressure, waist circumference (WC), pelvis circumference, body fat percentage, fasting levels of Triglyceride (TG), HDL-C, LDL-C, glucose, insulin, and lifestyle characteristics, including smoking and physical activity. SEP in childhood was based on father's occupation (scale 1–6) and in adulthood, on subject's occupation (scale 1–5). Additional analyses used maternal and subject's years of education. GLM and logistic regression models were used with mutual adjustment for SEP at both time points and further adjustment for gender, ethnic origin and fasting duration. Log transformation was used for TG and insulin levels. Results: Independently of current SEP, lower childhood SEP was significantly associated with higher logTG (β=0.013, p=0.042), higher LDL (β=1.979, p=0.023), higher body fat percentage (β=0.476, p=0.025) and higher odds of physical inactivity (OR=1.13, p=0.043). Independently of childhood SEP, lower adulthood SEP was significantly associated with lower HDL level (β=–0.934, p=0.026), higher WHR (β=0.006, p=0.002), and higher odds of smoking (OR=1.31, p=0.001) and physical inactivity (OR=1.34, p<0.0001). Significant interactions were found between SEP in both time points and LDL, WHR and WC (p for interactions=0.01, 0.024 and 0.055 respectively). The detrimental effect of lower SEP in adulthood on LDL level was strongest among subjects with high SEP in childhood (β=4.54, p<0.0001), compared with those having lower SEP in childhood. Similar trends were observed for WHR and WC (β=0.011, p<0.0001 and β=1.754, p=0.004 for associations of adulthood SEP with WHR and WC respectively, among subjects with high childhood SEP). Analyses, based on education as a measure of SEP, yielded similar interactive patterns. Conclusion: Adverse SEP at both childhood and adulthood has an independent influence on physiological and behavioral risk factors. The interaction between SEP in childhood and adulthood in their effect on cardiometabolic risk factors points to the important role played by social mobility in affecting adult poorer health.